ANALISIS KEMAMPUAN KEUANGAN DAERAH PEMERINTAH PROPINSI NUSA TENGGARA BARAT - Susanto, Hery (Jurnal Organisasi dan Manajemen, 2014)
This research aims to analyze the regional finance capability in West Nusa Tenggara province. This research uses secondary data of primary source. The data are obtained from the government of West Nusa Tenggara Province in the form of data that has been processed and published and become a legitimate document such as calculation data of APBD in Budgetary Year of 2003-2007. The instruments are used in collecting the data is the analysis of the regional finance capability through Calculation and Work Analysis of PAD, which is the measurement of share and growth, thus classified the result with mapping the financial region capability based on quadrant method. This research draws some conclusions namely: (1) generally, contribution of PAD (share) to the total region income of NTB Province TA 2003- 2007 was low, in spite of the growth of PAD was high; (2) based on the measurement of Index Financial Capability (IKK), NTB Province was in the scale index of 0,541. Furthermore, the classification based on the criteria level of regional finance capability, the regional finance capability in NTB Province in 2003 -2007 was a province with high financial capability. There are some suggestions that could be offered to the Government of NTB Province; first, improving PAD share in NTB Province through the excavation of PAD potential sources. Second, concerning with the region cost efficiency, considering that the proportion of PAD achievement was fairly small comparing to the allocation of Region Cost. Penelitian ini bertujuan untuk menganalisis kemampuan keuangan daerah di Propinsi Nusa Tenggara Barat . Penelitian ini menggunakan data sekunder dari sumber utama. Data diperoleh dari pemerintah Propinsi Nusa Tenggara dalam bentuk data yang telah diolah dan dipublikasikan dan menjadi dokumen yang sah seperti data perhitungan APBD Tahun Anggaran 2003-2007. Instrumen yang digunakan dalam pengumpulan data adalah analisis kemampuan keuangan daerah melalui Perhitungan dan Analisis Kerja PAD, yang merupakan pengukuran saham dan pertumbuhan, sehingga diklasifikasikan hasilnya dengan pemetaan kemampuan keuangan daerah berdasarkan metode kuadran. Penelitian ini menarik beberapa kesimpulan yaitu: (1) secara umum, kontribusi PAD (share) terhadap total pendapatan daerah Propinsi NTB TA 2003-2007 rendah, meskipun pertumbuhan PAD yang tinggi; (2) didasarkan pada pengukuran Kemampuan Index Keuangan (IKK), Propinsi NTB berada di indeks skala 0541. Selain itu, klasifikasi berdasarkan tingkat kriteria kemampuan keuangan daerah, kemampuan keuangan daerah di Propinsi NTB pada 2003-2007 adalah propinsi dengan kemampuan finansial yang tinggi. Ada beberapa saran yang dapat ditawarkan kepada Pemerintah Propinsi NTB; pertama, meningkatkan pangsa PAD di Propinsi NTB melalui penggalian potensi sumber PAD. Kedua, menyangkut dengan efisiensi biaya daerah, mengingat proporsi pencapaian PAD ini cukup kecil dibandingkan dengan alokasi biaya daerah